Implementasi Pelayanan Publik berbasis Electronic Government dalam Menghadapi Pandemi Covid-19 di Indonesia - Andi Fitri Rahmadany (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
The development of technology in Indonesia is very fast today. So that technology becomes a necessity that must be owned by everyone. Such as information technology that can be used by every community for their daily needs. Therefore, the government takes the opportunity to create quality services by utilizing information technology called e-government. the concept of e-government is the provision of public services that are good governance. Where all aspects contained in good governance are reflected in e-government. The researcher uses descriptive qualitative research using Miles and Huberman data analysis model. The parameter of e-government progress during the pandemic is that it has used a lot of application software on websites and information systems that support the implementation of office tasks and services to the community. The weakness is the management of information systems in some work units that focus on their respective fields of work. To improve e-government management, recommendations are given to integrate information systems for e-government management in order to improve the performance of public services.